Fathering in India Images and Realities - Sriram, Rajalakshmi (Springer Nature Singapore : Imprint: Springer, 2019)
This book covers the underexplored subject of 'fathering' in India. It delves into the shared aspirations of men in India to nurture their children in sensitively attuned ways within the culturally prescriptive context that governs men's roles as providers and caregivers. This work is based on over two decades of intensive research in India on how different groups construct and experience fatherhood and fathering under changing circumstances. It unmasks the heterogeneity that exists within fathering in India through conversations with fathers across diverse contexts-in privileged economic situations and those in difficult home and family circumstances, having children with disability, single-parent fathers and fathers in the military. A separate section discusses fathering daughters and shared parenting. Images and role models in fathering are brought alive through analysis of Hindi films, the media, children's literature and classical literature. The conceptual analysis moves beyond the power and control dimensions commonly used to describe Indian men and fathers, to highlight their resilience, adaptability, positive involvement and developmental trajectories. This volume is for scholars, researchers and practitioners in developmental psychology, human development and family science, sociology, early childhood education and psychiatry, pediatrics, community medicine and allied fields.